PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY TERHADAP PERSISTENSI LABA PADA PERUSAHAAN YANG BERGERAK DI SEKTOR ANEKA INDUSTRI DENGAN SUBSEKTOR MESIN DAN ALAT BERAT, OTOMOTIF DAN KOMPONEN, KABEL DAN ELEKTRONIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PAD - Amelinda Rosita; Juniarti Juniarti (Business Accounting Review, 2016)
The CSR influence on the financial performance that was periodically such as ROA, ROE and ROI have been done. However, research on the affects of CSR to the persistence of earnings that have been made in previous studies by Belkaoui (2004) and Lakshman and Yang (2009) had never been done in the Indonesian company sector Various Industries with subsector machines and weight, autos and parts, cables and electronics. The purpose of this study was to determine whether CSR affects the persistence of earnings in companies engaged in various industries Sector in the subsector machinery and equipment, automotive and components, cables and electronics. CSR was measured based on the GRI reporting criteria version 3.1 is 84 items. While the persistence of earnings measured by using a beta of koefien regression. This study used several variables that control the operating cycle, cash flow volatility, volatility of sales and the proportion of negative earningsThe data sample of 68 companies processed by using multiple linear regression method with SPSS. The results of this study proved that CSR had no affect on the persistence of earnings whereas, the other variables of the volatility of cash flow, sales volatility and the proportion of negative earnings had no affect on earning persistence. However, the operating cycle affect on earnings persistence.